Influence of the digital economy on dissemination of non-cash trading - Jagodzińska-Komar, Ewa (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2019)
The aim of the article is to assess the influence of the digital economy on the popularisation of non-cash trading in Poland as well as to indicate actions intended to help Poland join the group of digitalisation leaders. What is drawn attention to in the first place is the establishment on the Polish market of a new entity – the Polish Cashless Foundation, which is responsible for disseminating the idea of non-cash trading through the development of a payment cards accepting network. The article describes the position of Poland against the background of other member states of the European Union in terms of the digitalisation progress in 2017. One of the elements which could improve the DESI index (the digital economy and society index) is the development of electronic administration, which is assessed subsequently. The article proceeds to present the results of research concerning digital payment innovations conducted by two largest international payment organizations, VISA and Master Card, which shows that Polish society is more and more willing to make use of innovative payment instruments.